UTILIZATION OF BLOTONG AS AN ACTIVATOR ORGANIC FERTILIZER - Ali, Munawar; Mirwan, M. (Ikatan Dosen Menulis, 2021)
Utilizing microbial activity to transform organic waste into material with the characteristics of soil, composting is a method of biological treatment of organic waste. Sugar factory filter cake contains minerals like carbon, nitrogen, phosphate, calcium, and others that can be used to recover soil, such as a high-water holding capacity. Green manure made from organic waste is the goal of the research. Filter cake is the waste from the sugar factory mixed with trash. The aerobic system used in this study adds 1 kg, 2 kg, 3 kg, and 4 kg of filter cake, respectively. The dosage options for the aeration method, both without and with an aerator, are 1.8; 2,7 and 3,6 l/min/kgVs. Rubbish without a filter cake and weighing 3 kg serve as a control. The study found that a C/N ratio of 19.2 was decreased when 4 kg of filter cake was added to each 3 kg of trash stimulation. The air circulation strategy that is powerful for treating the soil is to utilize an aerator. During composting, the microbial growth influences a decrease of 84% in the C/N ratio.